2010
DOI: 10.1007/s11069-010-9520-y
|View full text |Cite
|
Sign up to set email alerts
|

Micro-scale flood risk analysis based on detailed 2D hydraulic modelling and high resolution geographic data

Abstract: inundation modelling as well as on high resolution topographic and land use database.The flow model is based on the shallow-water equations, solved by means of a finite volume scheme on multiblock structured grids. Using highly accurate laser altimetry, the simulations are performed with a typical grid spacing of 2m, which is fine enough to represent the flow at the scale of individual buildings.Consequently, the outcomes of hydraulic modelling constitute suitable inputs for the subsequent exposure analysis, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(107 citation statements)
references
References 28 publications
0
90
0
12
Order By: Relevance
“…Ernst et al (2010) assessed high-resolution economic damage (2 m × 2 m) along two sections of the river Ourthe, a tributary of the Meuse in Belgium. Wind et al (1999) reported observed (direct) damage in Dutch Limburg for the flood events of 1993 and 1995 of about C149 million (1993) and C91 million (1995) 1 (in year 2000 euros).…”
Section: Past Research On Flood Risk In the Meuse Basinmentioning
confidence: 99%
“…Ernst et al (2010) assessed high-resolution economic damage (2 m × 2 m) along two sections of the river Ourthe, a tributary of the Meuse in Belgium. Wind et al (1999) reported observed (direct) damage in Dutch Limburg for the flood events of 1993 and 1995 of about C149 million (1993) and C91 million (1995) 1 (in year 2000 euros).…”
Section: Past Research On Flood Risk In the Meuse Basinmentioning
confidence: 99%
“…Developed countries, where anthropic settlements determined extensive urbanization processes, have to deal with an existing building stock located in hazard prone areas which is not always «hazards proofed» and is ageing: such built assets require the implementation of mitigation and protection measures against natural threads that are continuously evolving due to the current global climate change. Several references provide lists of parameters to be considered in the evaluation of vulnerability (Federal Emergency Management Agency, 2007) (Van Westen et al 2008) and fine grain analysis on buildings vulnerability are not new in the scientific panorama (Sucuoğlu et al, 2007) (Ernst et al, 2010) (Stephenson et al, 2014).…”
Section: Use Casesmentioning
confidence: 99%
“…The time step is adaptive and computed based on the Courant-Friedrichs-Lewy (CFL) stability criterion, with a CFL number equal to 0.5. It takes values of the order of 10 -3 -10 -2 s. This finite volume model has already proven its validity and efficiency for the analysis of natural and artificial floods (Ernst et al, 2010;Erpicum et al, 2010a;Dewals et al, 2011), as well as numerous other applications including complex turbulent flows (Dewals et al, 2008;Erpicum et al, 2009;Roger et al, 2009;Dufresne et al, 2011).…”
Section: Numerical Modelmentioning
confidence: 99%